Food Security Level of Male Headed Households and Female Households - Yulyanti Fathonah, Tri; W. Prasodjo, Nuraini (Sodality: Jurnal Sosiologi Pedesaan, 2011)
The purpose of this research was to determine the level of food security in both types of households, namely male headed households (RTKP) and female headed households (RTKW). The objective of this research are male headed households (RTKP) and female headed households (RTKW) ) in Jembatan Serong Community. The research methode uses a quantitative approach to survai research that is supported by qualitative data. The respondents were selected by applying simple random sampling technique. The results of this study showed that households in Jembatan Serong Community belong to the category of food security and food security inequality do not occur in RTKP and RTKW. Based on cross tabulation, the education of food administrators of RTKP and RTKW associated with the level of food security and income levels RTKP and RTKW associated with the level of food security